Novel SKIC3 variants in tricho-hepato-enteric syndrome with hemochromatosis - Ochiai, Kayo; Aoki, Yoshinori; Yamada, Naoshi; Aman, Murasaki; Yamashita, Atsushi; Yamaguchi, Masatoshi; Nakato, Daisuke; Takenouchi, Toshiki; Kosaki, Kenjiro; Kodama, Yuki; Moritake, Hiroshi (Human genome variation, 2025)
Tricho-hepato-enteric syndrome (THES), a rare autosomal recessive disorder caused by variants in the SKIC3 or SKIC2 gene, is characterized by intractable diarrhea, woolly hair, growth restriction and liver disease. Here we report a neonatal case of THES with neonatal hemochromatosis, in which the novel compound heterozygous SKIC3 variants NM_014639.4:c.815_816del p.(Gly272AlafsTer9) and NM_014639.4:c.2284G>A p.(Gly762Arg) were identified. Further research is needed to elucidate the mechanisms underlying iron metabolism dysregulation in THES.